HUBUNGGAN ANTARA KEKUATAN OTOT KAKI TERHADAP KETETEPAN HASIL JUMPT SHOOT PADA PERMAINAN BOLA BASKET DI TEAM BARA PUTRA LUBUKLINGGAU - Hengky Remora; Wawan Syafutra ($$8@@&&$%K, 2022)
The purpose of this study was to find out whether there is a relationship between leg muscle strength and the accuracy of the Jump Shoot results in a basketball game at the Bara Putra Lubuklinggau club in 2021. The variables in this study were leg muscle strength as the independent variable and the results of the Jump Shoot as the dependent variable. The sample in this study used the entire population, namely 20 athletes. The method used in this study is the correlational method. The data collection technique consists of documentation, test techniques, data analysis techniques, and hypothesis testing used, namely the "t" test with a significant level of α = 0.05. The conclusion from the results of the study states that leg muscle strength has a relationship between leg muscle strength and the accuracy of the Jump Shoot results in a basketball game at the Bara Putra Lubuklinggau club in 2021, with the results of testing the hypothesis using the "t" test significant level α = 0.05 obtained value and so, > . It means that Ho is rejected and Ha is accepted, stating that there is a relationship between leg muscle strength and the accuracy of the Jump Shoot results in the basketball game at the Bara Men's Club in 2021. because the conditions for Ho are accepted if and Ha are accepted at another price